Colonialism, water and the Black body. (1st June 2020) - Gooden, Mario
For the Black body, water is a topological condition that has been a medium for European colonialism and the construction of race illustrated in the earliest fifteenth century Portuguese nautical master charts depicting the latest knowledge of African coastlines by the transport of enslaved Africans to the shores of the 'new world' in North America, South America and the Caribbean, as a means of delineating spatial separation through segregated water fountains, swimming pools and beaches in the United States and South Africa; by the forced migration of people of colour due to sea-level rise and disastrous typhoons and hurricanes such as Irma, Maria, Harvey and most recently Dorian ‐ all the result of global climate change induced by centuries-old pollution in the industrialized nations of Europe and North America; by the lack of access to clean drinking water not only in former European colonies in Africa but also in cities such as Flint, Michigan and Newark, NJ, and to the paucity of water and severe drought in places like the former Portuguese colony of Cape Verde as well as Cape Town, South Africa, formerly colonized by the Dutch and the British. Water as a line from coloniality to climate change represents the spectacle of vulnerability within the quotidian condition of Black life and its indigeneity and diasporic formation linked by a vicious history of imperialism and colonization. The topology of water refers to not only geometric properties of water in terms of its liquidity, flows, movement and capacity for infinite temporal and morphological containments but also the cultural landscape of water defined by relationships of power that do not so much change but take up new guises of privilege and subjugation.